Pasture plants of central Italy and possible traceable compounds in sheep cheese - Pratesi V.; Ghiselli L.; Pardini A.; Buccioni A.; Vecchio V. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Italian food is known for its taste and quality, but often too expensive to compete on the market. However, the greater quality and better taste of Italian food products, compared to food products from conventional agriculture, attract considerable interest from customers, and as a consequence certified organic, biodynamic and typical food products show interesting added value on the market. One of the problems with these food products is the traceability of the product from the point of origin to the customers. A research has been conducted about pasture plants that might be traced down to the final sheep caciotta cheese Pecorino Toscano. Three farms have been chosen in central Italy, each with different levels of pasture complexity, one farm on a flat area (simple botanical composition), one on a hill (medium specific diversity), and one in the mountains (highly diverse pastures). The botanic composition of all the pastures of the three farms was analysed using a linear analysis, and a list of common species was extrapolated, the most preferred species were Bromus sterilis, Lolium perenne and L. multiflorum. Finally, a list of species is given with some data about possible traceable compounds. Analyses of macro- and micro-elements by optical emission spectrometer (ICP-OES) and elemental analyzer (CHN), and of flavonoids and terpenes (HPLC) are now in progress.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)